1986
DOI: 10.1080/09553008614551391
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Procaine and Phenethyl Alcohol on Excision Repair of DNA in u.v.-irradiatedEscherichia Coli

Abstract: Experiments were performed to investigate the involvement of the cell membrane in the excision DNA repair process in Escherichia coli. Two membrane-binding drugs, procaine and phenethyl alcohol (PEA), inhibited liquid-holding recovery (LHR) in u.v.-irradiated E. coli wild-type and recA strains. In uvrB and polA strains where, after u.v.-irradiation, LHR was absent the two drugs had no effect. Both drugs markedly reduced the removal of u.v.-induced thymine dimers in the DNA of wild-type cells (H/r30). Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The UvrB subunit is a hydrophobic protein, which is cleaved by a membranebound protease (32,33). Yonei and co-workers, in a series of papers, have shown that membrane-disrupting drugs such as lidocaine, procaine, and phenethyl alcohol inhibit nucleotide excision repair (237,238,240). Phenethyl alcohol, which clearly disrupts the DNA-membrane association, was shown to inhibit the incision step, whereas procaine, which does not inhibit the membrane-DNA associations, was shown to inhibit a later excision or resynthesis step (240).…”
Section: Intracellular Site Of Dna Repairmentioning
confidence: 99%
“…The UvrB subunit is a hydrophobic protein, which is cleaved by a membranebound protease (32,33). Yonei and co-workers, in a series of papers, have shown that membrane-disrupting drugs such as lidocaine, procaine, and phenethyl alcohol inhibit nucleotide excision repair (237,238,240). Phenethyl alcohol, which clearly disrupts the DNA-membrane association, was shown to inhibit the incision step, whereas procaine, which does not inhibit the membrane-DNA associations, was shown to inhibit a later excision or resynthesis step (240).…”
Section: Intracellular Site Of Dna Repairmentioning
confidence: 99%